2020
DOI: 10.1001/jamacardio.2019.5850
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostic Models Derived in PARADIGM-HF and Validated in ATMOSPHERE and the Swedish Heart Failure Registry to Predict Mortality and Morbidity in Chronic Heart Failure

Abstract: IMPORTANCEAccurate prediction of risk of death or hospitalizations in patients with heart failure (HF) may allow physicians to explore how more accurate decisions regarding appropriateness and timing of disease-modifying treatments, advanced therapies, or the need for end-of-life care can be made. OBJECTIVE To develop and validate a prognostic model for patients with HF. DESIGN, SETTING, AND PARTICIPANTS Multivariable analyses were performed in a stepwise fashion. Harrell C statistic was used to assess the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 21 publications
2
79
0
2
Order By: Relevance
“…[33][34][35] Intriguingly, EF was not found to be a significant independent prognostic factor, which is in line with the BCN Bio-HF study, but not with the latest prognostic analysis in HF, that is, PARADIGM-HF (Simpson et al reported a 7% decrease in mortality rate for every 5% increase of EF). 36 Similarly, BB usage was not a crucial factor (probably due to the high rate of use of this treatment in both survivors and non-survivors). As in the BCN Bio-HF, we did not find other HF therapies in the HF cohort to have any significant impact on outcomes in DCM (via multivariate analysis).…”
Section: The Development Of a Mortality Calculator Tailored For Dilated Cardomyopathymentioning
confidence: 99%
“…[33][34][35] Intriguingly, EF was not found to be a significant independent prognostic factor, which is in line with the BCN Bio-HF study, but not with the latest prognostic analysis in HF, that is, PARADIGM-HF (Simpson et al reported a 7% decrease in mortality rate for every 5% increase of EF). 36 Similarly, BB usage was not a crucial factor (probably due to the high rate of use of this treatment in both survivors and non-survivors). As in the BCN Bio-HF, we did not find other HF therapies in the HF cohort to have any significant impact on outcomes in DCM (via multivariate analysis).…”
Section: The Development Of a Mortality Calculator Tailored For Dilated Cardomyopathymentioning
confidence: 99%
“…9,14 CHARM also showed that total bilirubin, which was the strongest predictor among the liver function tests in the present study, and ALP were associated with an increased risk of the composite endpoint (CV death and HF hospitalization), consistent with our results. Importantly, Simpson et al 18 showed that total bilirubin was included as one of the important predictors in a comprehensive HFrEF prognostic model based on PARADIGM-HF.…”
Section: Conventional Liver Function As Predictors For Cardiovascularmentioning
confidence: 99%
“…В силу мультиколлинеарности между факторами риска парциальное прогностическое значение каждого из них определить сложно и, следовательно, непросто отличить действительно значимые независимые предикторы от случайно выявляемых и не несущих дополнительной информации. Выходом из проблемной ситуации в клинической практике может быть применение многофакторных моделей прогноза, которые, по понятным причинам, имеют преимущества перед монофакторными [9,54,55].…”
Section: критерии диагностикиunclassified